Investigating Risk of Organic Rice Production in Kapanewon Prambanan: Comparative Study with Non-Organic Rice Farming - Aisyah, Dinda Dewi; Dhamira, Aura; Albab, Azizah Ridha Ulil (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2024)
The transition from conventional farming to organic continues to increase over time. Organic farming, especially organic rice, is becoming something that farmers are interested in because of higher prices and increased consumer demand for organic food products. However, the transition to conventional farming will eventually be followed by the emergence of risks in farming production. This study investigates the factors influencing the production and production risks of organic and non-organic rice farming in Sleman Regency. A total of 45 farmers were sampled in this study, which was determined by purposive sampling. Data collection was carried out by interview method. The Just and Pope approach of production risk is used in analyzing the determinants of production and production risk. The analysis results show that the membership period in farmer groups, land area, education, and manure significantly affects farming production. At the same time, organic rice farming is proven to produce higher production than non-organic. The factor that significantly increases production risk is the length of membership in farmer groups. Farmers who join farmer groups have the potential to face higher production risks. This research implies that it is important for the government to provide support by empowering farmer groups to support organic rice farming. Intensive assistance can be carried out to ensure that the role of the chairperson and members of the farmer group functions optimally.